2010
DOI: 10.1258/acb.2010.010040
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial plasma bile acid responses in normal weight and obese subjects

Abstract: The decreased postprandial bile acid response in obese subjects compared with normal weight subjects may partly explain the suboptimal GLP-1 and PYY responses and could affect appetite, glycaemic control and energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 7 publications
6
69
0
Order By: Relevance
“…Patients after bariatric surgery to correct for obesity have higher circulating levels of BAs, which are positively correlated with metabolic improvements (40,41). This latter observation was recently confirmed in obese patients, who have a decreased postprandial BA response in comparison with normal weight subjects (42). In contrast to this body of evidence that suggests that increasing BA levels benefit metabolic homeostasis, GW4064 decreased the expression levels of genes involved in energy expenditure in BAT, underscoring that these effects are not directly caused by FXR activation but rather are the consequence of reduced TGR5 activation subsequent to the reduction in the BA pool.…”
Section: Discussionmentioning
confidence: 73%
“…Patients after bariatric surgery to correct for obesity have higher circulating levels of BAs, which are positively correlated with metabolic improvements (40,41). This latter observation was recently confirmed in obese patients, who have a decreased postprandial BA response in comparison with normal weight subjects (42). In contrast to this body of evidence that suggests that increasing BA levels benefit metabolic homeostasis, GW4064 decreased the expression levels of genes involved in energy expenditure in BAT, underscoring that these effects are not directly caused by FXR activation but rather are the consequence of reduced TGR5 activation subsequent to the reduction in the BA pool.…”
Section: Discussionmentioning
confidence: 73%
“…The relevance of our findings for man remains to be elucidated. However, it has been reported that obese subjects had a lower post-prandial bile acid response, relative to normal weight subjects (80). Furthermore, subjects that had previously undergone gastric bypass showed higher circulating bile acid levels, relative to both obese and severely obese objects.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, relevant to obesity is the observation that bile salts act as 'nutrient signalling molecules' in a feed/fast cycle controlling the flow of absorbed molecules after meals. This could be of considerable interest if there was a postprandial reduced bile response in obese individuals as reported by Glicksman et al 1 FXR is essential in the feed/fast cycle and inhibition of glycolysis and may lower triglycerides by enhanced very-low-density lipoprotein production turnover and lipoprotein lipase activation. FXR also is implicated in the downregulation of hepatic fatty acid and triglyceride biosynthesis mediated by sterolregulatory-element-binding protein 1c.…”
mentioning
confidence: 89%